2003
DOI: 10.1007/s00294-002-0356-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of spontaneous mutants of Magnaporthe grisea expressing stable resistance to the Qo-inhibiting fungicide azoxystrobin

Abstract: The class of Qo-inhibiting fungicides (QoIs) act as respiration inhibitors by binding to the Qo center of cytochrome b. The longevity of these fungicides has been challenged by the selection of fungal sub-populations resisting high doses of QoI fungicides, with a G143A amino acid exchange in the cytochrome b target site identified as the most common cause of resistance. In contrast, the mechanism of alternative respiration, as another mechanism of fungal QoI resistance, has thus far not been affiliated with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 14 publications
7
73
0
Order By: Relevance
“…The concentration of ROS is known to increase under the action of Q o site inhibitors, and this may in turn increase the rate of mutagenic oxidation (18). Potentially increased mutation rates in response to inhibitor action conform to the concept of ''adaptive mutations'' (19,20), rather than supporting the model of constant rare mutations leading to preexisting phenotypes expressing resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of ROS is known to increase under the action of Q o site inhibitors, and this may in turn increase the rate of mutagenic oxidation (18). Potentially increased mutation rates in response to inhibitor action conform to the concept of ''adaptive mutations'' (19,20), rather than supporting the model of constant rare mutations leading to preexisting phenotypes expressing resistance.…”
Section: Discussionmentioning
confidence: 99%
“…One year later, the development of field-reduced sensitivity to azoxystrobin in populations of the plant pathogen Mycosphaerella fijiensis was first observed (49). As for other single-site inhibitors, the longevity of QoI fungicides was thus quickly challenged in the field, and resistant isolates have been described for numerous plant pathogen species, such as Alternaria solani, Blumeria graminis, Mycosphaerella graminicola, Plasmopara viticola, Podosphaera fusca, Puccinia species, Magnaporthe oryzae, and Venturia inaequalis (5,21,22,30,33,35,38,44,49,50,52,54,56). In most cases, resistance to QoI fungicides is conferred by a point mutation in the mitochondrial cytochrome b gene, giving rise to a substitution from glycine to alanine at position 143 (G143A) of the amino acid sequence (25,29,35).…”
mentioning
confidence: 99%
“…This high variability has also been observed in M. fructicola isolates with reduced sensitivity to propiconazole (Cox et al, 2007). In most studies on QoI-resistant fungi, pathogens with a mutation at codon 143 showed, qualitatively, stable resistance following successive transfers in non-amended media, such as in azoxystrobin-resistant Magnaporthe grisea (Avila-Adame and Koller, 2003), Didymella bryoniae isolates (Finger et al, 2013) and pyraclostrobin-resistant Venturia inaequalis isolates (Frederick et al, 2014). Botrytis cinerea isolates resistant to boscalid and pyraclostrobin exhibited stable resistance after as many as 20 transfers (Kim and Xiao, 2011).…”
Section: Resultsmentioning
confidence: 94%